Using a lighter to heat a cautery - Brian Savage (Community Eye Health Journal, 2011)
Those of us who are extracapsular cataract surgeons have all experienced delays in cauterizing the eye due to difficulty in lighting a spirit lamp containing methylated spirit with too much water mixed in it. We have found that using a cigarette lighter for heating is a viable alternative.